Coronavirus disease-19 spread in the Eastern Mediterranean Region, updates and prediction of disease progression in Kingdom of Saudi Arabia, Iran, and Pakistan - Sharif, Asmaa Fady; Mattout, Sara Kamal; Mitwally, Noha Adel (International Journal of Health Sciences, 2020)
Objectives: The present study is considered the first study that aims to estimate the spread of COVID-19 pandemic in the Eastern Mediterranean Region and to predict the pattern of spread among KSA in comparison to Iran and Pakistan. Methodology: Data during the period from 29 January till 14 April 2020 was extracted from 76 WHO situational reports and from the Worldometer website. Numbers of populations in each country was considered during data analysis. SIRD Model and Smoothing Spline Regression model were used to predict the number of cases in each country. Results: SIRD model in KSA yieldedβ = 2e-0.6, γ = 0.006 and m= 0.00038 and R0= 0.00029. It is expected that by the 1st of May 2020 that number of cumulative infected cases would rise to 16848 in KSA, and to 11825 in Pakistan while in Iran, it is expected that the number mostly will be100485. Moreover, the basic reproduction number R0 is expected to decrease by time progression. Conclusion: The cumulative infected cases are expected to grow exponentially. Although R0 is expected to be decreased, the quarantine measures should be maintained or even enhanced.